O encontro com a história de vida de uma mulher benzedeira - Oliveira, Débora (Universidade Federal de São Carlos, 2018)
This is a work and process of receiving memories and their resonances (BENJAMIN, 1994), which are welcome and known through access to the life story of a woman who is a healer. A Language, 2016) becomes an important field for a reflection that transits from intuitive knowledge (LARROSA, 2016) becomes an important area for a reflection that transitions from intuitive knowledge (BERGSON, 1979; MERLEAU-PONTY, 1984) to process of flavors exchange, of a tradition that is not what is the case, but also of a process of non-school education, but of an emergent education of the people about a life, allowing itself to be configured in the recovery of the value of a tradition of know-how, as well as a reality that is an emancipation of life (FREIRE, 1980). The objective is to create a research and the dissemination of market opportunities for an oral history (BOSI, 1981).
The encounter with the life story of a heals woman
Keywords: Memórias; História de vida; Saber da experiência; História oral; Memories; Life’s history; Intuitive knowledge; Knowledge of experience; Oral history; Curandeiras; Women healers; CIENCIAS HUMANAS::EDUCACAO